New advances in the treatment of generalized lipodystrophy: role of metreleptin - Rodriguez AJ; Mastronardi CA; Paz-Filho GJ (Dove Medical Press, 2015)
Alexander J Rodriguez,1 Claudio A Mastronardi,2 Gilberto J Paz-Filho2 1Department of Medicine, Monash Medical Centre, Clayton, VIC, 2Department of Genome Sciences, The John Curtin School of Medical Research, The Australian National University, Canberra, ACT, AustraliaAbstract: Recombinant methionyl human leptin or metreleptin is a synthetic leptin analog that has been trialed in patients with leptin-deficient conditions, such as leptin deficiency due to mutations in the leptin gene, hypothalamic amenorrhea, and lipodystrophy syndromes. These syndromes are characterized by partial or complete absence of adipose tissue and hormones derived from adipose tissue, most importantly leptin. Patients deficient in leptin exhibit a number of severe metabolic abnormalities such as hyperglycemia, hypertriglyceridemia, and hepatic steatosis, which can progress to diabetes mellitus, acute pancreatitis, and hepatic cirrhosis, respectively. For the management of these abnormalities, multiple therapies are usually required, and advanced stages may be progressively difficult to treat. Following many successful trials, the US Food and Drug Administration approved metreleptin for the treatment of non-HIV-related forms of generalized lipodystrophy. Leptin replacement therapy with metreleptin has, in many cases, reversed these metabolic complications, with improvements in glucose-insulin-lipid homeostasis, and regression of fatty liver disease. Besides being effective, a daily subcutaneous administration of metreleptin is generally safe, but the causal association between metreleptin and immune complications (such as lymphoma) is still unclear. Moreover, further investigation is needed to elucidate mechanisms by which metreleptin leads to the development of anti-leptin antibodies. Herein, we review clinical aspects of generalized lipodystrophy and the pharmacological profile of metreleptin. Further, we examine studies that assessed the safety and efficacy of metreleptin, and outline some clinical perspectives on the drug. Keywords: metreleptin, leptin, lipodystrophy, pharmacology, adipose tissue